VLSI-SoC : design and engineering of electronics systems based on new computing paradigms : 26th IFIP WG 10.5/IEEE International Conference on Very Large Scale Integration, VLSI-SoC 2018, Verona, Italy, October 8-10, 2018, Revised and extended selected papers /: design and engineering of electronics systems based on new computing paradigms : 26th IFIP WG 10.5/IEEE International Conference on Very Large Scale Integration, VLSI-SoC 2018, Verona, Italy, October 8-10, 2018, Revised and extended selected papers. (2019) - Unknown
No abstract available